Student ultrasound education – current views and controversies - Dietrich, Christoph F.; Sirli, Roxana Lucia; Barth, Gregor; Blaivas, Michael; Daum, Nils; Dong, Yi; Essig, Manfred; Gschmack, Anna Maria; Goudie, Adrian; Hofmann, Tino; Hoffmann, Beatrice; Jenssen, Christian; Kallenbach, Michael; Karlas, Thomas; Krutz, Alexander; Löwe, Axel; Lucius, Claudia; Möller, Kathleen; Neubauer, Ricarda; Nurnberg, Dieter; Prats, Michael; Prosch, Helmut; Recker, Florian; Ruppert, Johannes P.; Sänger, Sophie-Luise; Wangenheim, Friederike; Weimer, Johannes M.; Westerway, Susan Campbell; Zervides, Constantinos (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
As an extension of the clinical examination and as a diagnostic and problem-solving tool, ultrasound has become an established technique for clinicians. A prerequisite for high-quality clinical ultrasound practice is adequate student ultrasound training. In light of the considerable heterogeneity of ultrasound curricula in medical studies worldwide, this review presents basic principles of modern medical student ultrasound education and advocates for the establishment of an ultrasound core curriculum embedded both horizontally and vertically in medical studies.
Keywords: METHODS & TECHNIQUES; ultrasound; Education, Training, Quality Assurance; student